Piperine Induces Cell Death, Apoptosis and Inhibits Migration in Cholangiocarcinoma Cells - Buranrat, Benjaporn; Senggunprai, Laddawan; Prawan, Auemduan; Kukongviriyapan, Veerapol (Indian Journal of Pharmaceutical Education and Research, 2023)
Background/Aim: Piperine (Pip) is an alkaloid that found from natural products and it has been reported to exert anticancer activities. Nevertheless, its anticancer effect has not yet been illustrated in cholangiocarcinoma (CCA) cells. In this work will be explored the Pip effects on two CCA cells and studied the underlying molecular mechanism. Materials and Methods: The KKU-100 and KKU-M452 cells proliferation were detected by sulforhodamine B assay, colony formation, and flow cytometric method. Migratory ability was explored via the wound healing and Transwell chamber model. Apoptosis was discovered through double staining of PI and Annexin V-FITC dye. JC-1 dye, and DCF-DA staining by flow cytometry. Results: The results revealed that Pip induced CCA cells death by a dose‑ and time-dependent along with inhibiting colony formation in KKU-100 cells. Following cell cycle arrest, treatment with Pip arrested the cell cycle distribution at G0/G1 phase in KKU-100 and S to G2/M phase in KKU-M452 cells. Furthermore, cell migration revealed that Pip suppressed cell migration in a dose‑dependent manner. Apoptosis was significant detected by flow cytometry showed that Pip induced late apoptosis in these two CCA cells. The mechanism was indicated that Pip treatment also decreased mitochondrial membrane potential and increased ROS formation. Conclusion: Therefore, Pip may useful for prevention and treatment of CCA.
Keywords: Piperine; Apoptosis; Migration; Cholangiocarcinoma cells; Mitochondrial function; Reactive oxygen species production